Deciphering decidual leukocyte traffic with serial intravascular staining - Vazquez, Jessica; Mohamed, Mona A.; Banerjee, Soma; Keding, Logan T.; Koenig, Michelle R.; Leyva Jaimes, Fernanda; Fisher, Rachel C.; Bove, Emily M.; Golos, Thaddeus G.; Stanic, Aleksandar K. (Frontiers in Immunology, 2024)
The decidual immunome is dynamic, dramatically changing its composition across gestation. Early pregnancy is dominated by decidual NK cells, with a shift towards T cells later in pregnancy. However, the degree, timing, and subset-specific nature of leukocyte traffic between the decidua and systemic circulation during gestation remains poorly understood. Herein, we employed intravascular staining in pregnant C57BL/6J mice and cynomolgus macaques (Macaca fascicularis) to examine leukocyte traffic into the decidual basalis during pregnancy. Timed-mated or virgin mice were tail-vein injected with labelled aCD45 antibodies 24 hours and 5 minutes before sacrifice. Pregnant cynomolgus macaques (GD155) were infused with labelled aCD45 at 2 hours or 5 mins before necropsy. Decidual cells were isolated and resulting suspensions analyzed by flow cytometry. We found that the proportion of intravascular (IVAs)-negative leukocytes (cells labeled by the 24h infusion of aCD45 or unlabeled) decreased across murine gestation while recent immigrants (24h label only) increased in mid-to lategestation. In the cynomolgus model our data confirmed differential labeling of decidual leukocytes by the infused antibody, with the 5 min infused animal having a higher proportion of IVAs+ cells compared to the 2hr infused animal. Decidual tissue sections from both macaques showed the presence of intravascularly labeled cells, either in proximity to blood vessels (5min infused animal) or deeper This is a provisional file, not the final typeset article into decidual stroma (2hr infused animal). These results demonstrate the value of serial intravascular staining as a sensitive tool for defining decidual leukocyte traffic during pregnancy.